IMPACT ANALYSIS AND DIRECTIONS OF ENVIRONMENTAL MANAGEMENT BASED ON THE LIME STONE MINING PROCESS FOR THE COMMUNITY IN KANAGARIAN KAMANG MUDIAK, KAMANG MAGEK DISTRICT - Tiara suci ramadhani; Zamhar Bakri; Alexander Syam (Lembaga Penelitian dan Pengabdian Kepada Masyarakat STKIP Ahlussunnah, 2022)
This research was conducted to determine the impact of limestone mining on the environment for the community in Kenagarian Kamang Mudiak, Kamang Magek District. The method of data collection in this study used a qualitative descriptive method which was complemented by a quantitative data analysis method. Data were collected based on the results of observations, questionnaires / questionnaires, interviews and equipped with documentation. This research was conducted in Kenagarian Kamang Mudiak, Kamang Magek District, namely 765 people, in this case as the research population. Data analysis used descriptive data analysis of the Miles and Huberman model and was equipped with quantitative data analysis through data weighting. Based on the data analysis carried out, it was found that: 1) There was a decrease in community income and the condition of accessibility of the distribution channel of mining products that affected the community, this was supported by the results of a weighting analysis with an initial value of 5 to 1 so that the criteria decreased in value, 2) Management direction which can be recommended as an effort to deal with the impact on the community are a) Strengthening community agricultural potential, b) Management strategy by strengthening regional potential.